Livelihood assets and food security achievement: an empirical study of the coastal fishermen in northern peninsular Malaysia - Ibrahim, Ahmad Zubir; Hassan, Kalthum; Kamaruddin, Roslina; Anuar, Abdul Rahim (2018)
The aim of this study is to analyze the food security achievement among coastal fishermen in Northern Peninsular Malaysia (Kedah and Perlis,) based on ownership livelihood asset. For this purpose, a structured questionnaire is designed. It consists of livelihood asset (human, physical, finance, natural and social asset), government intervention and livelihood outcome. To achieve the aim of the study, data were collected from a sample of 400 coastal fishermen in Kuala Kedah, TanjungDawai and Yan in Kedah and Kuala Perlis in Perlis Malaysia. The smart PLS-SEM 2.0 was used to evaluate the relationship between the independent and dependent variables. This study discovers that 4 out of the 6 hypotheses were supported by the statistical analysis while 2 hypotheses were not supported. Lastly, a few recommendations were provided with a view to ensuring food security among the coastal fishermen in Northern Peninsular Malaysia.